A journey through the neighborhoods outside the walls of Havana in the maps of the Spanish archives (1763-1834) - Azorín García, Eduardo (2023)
This article analyzes a series of urban plans, collected from Spanish archival collections, of the suburbs of Havana with the aim of knowing the transformation and growth of this space. The cartographies presented show that the expansion of these suburbs was a major problem for the land defense of the city. To contain this problem, numerous provisions were implemented. However, the increase in the suburbs was unstoppable and the circumstance led to new defense and urban projects to safeguard the interests of the population settled outside the wall.